Effects of Nanoconﬁnement on Catalysis - Poli, Rinaldo (Springer International Publishing : Imprint: Springer, 2017)
This book highlights the recent advances and state of the art in the use of functionalized nanostructured environments on catalysis. Nanoconfinements considered include well-defined molecular cages, imprinted self-assembled supramolecules, polymers made by living or controlled polymerization, metallorganic frameworks, carbon nanotubes, mesoporous inorganic solids, and hybrids thereof. Advantages of nanoconfinement of catalysts discussed include higher activities, improved selectivities, catalyst stabilization, cooperativity effects, simplified protocols for cascade syntheses, better catalyst recovery, and recyclability. The multiple applications that these materials offer are revolutionizing industrial sectors such as energy, electronics, sensors, biomedicine, and separation technology.
Keywords: Chemistry.; Catalysis.; Nanochemistry.; Nanotechnology.; elektronické knihy; electronic books